Pancytopenia caused by iron-dextran. Issue 2 (February 1986) - Hurvitz, H; Kerem, E; Gross-Kieselstein, E; Brand, A; Branski, D
Abstract : Pancytopenia after intramuscular iron-dextran treatment occurred in an infant with Down's syndrome. Haematological abnormalities recurred on subsequent challenge. Positive migration inhibiting factor and mast cell degranulation tests support an allergic pathogenesis for the pancytopenia. These side effects have not been reported previously.